Unlocking Critical Thinking: The LCI Learning Model for Pre-Service Elementary School Teacher - Yulia Eka Yanti; Tety Nur Cholifah; Hendra Rustantono; Hamidi Rasyid (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the effectiveness of the Learning Cycle-Inquiry (LCI) model in enhancing critical thinking skills among pre-service elementary school teachers in remote areas of Malang, Indonesia. The development of critical thinking skills is fundamental for educational success and effective problem-solving in real-world scenarios. Despite its recognized importance, the cultivation of these skills remains insufficiently addressed in Indonesia's educational practices, especially among pre-service teachers destined for elementary education in remote locales. To address this deficiency, a quasi-experimental research design was implemented, involving 82 pre-service teacher students distributed across four classes. These classes were systematically assigned to either the LCI model, the learning cycle, inquiry-based methods, or conventional teaching strategies. The effectiveness of these methods was measured using ANCOVA and LSD statistical analyses. The findings revealed that the LCI model significantly improved critical thinking skills (p 0.001), outperforming other educational approaches, with a corrected mean value of 84.39. These results underscore the potential of the LCI model to substantially boost critical thinking capabilities and suggest its wider adoption could enhance educational outcomes in similar settings.